Evaluasi Kepuasan Pengguna Pada Website Beasiswa Universitas Brawijaya Menggunakan Metode End-User Computing Satisfaction (EUCS) - Teuku Yusuf Ryan Ar-Rasyid; Buce Trias Hanggara; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The Brawijaya University Scholarship Website is a website that functions as a scholarship information search page where the students of Brawijaya University can find out the stipulated scholarship requirements, Brawijaya University scholarship website acts as an intermediary between scholarship providers and students who wish to get scholarships. But in fact, there are often problems with the website and the quality of the website also has disadvantages that are felt by its users, for example, the website pages are relatively old, the writing on the website is too monotonous, and scholarship information is late to be disseminated. This study aims to improve the quality of the Brawijaya University Scholarship website so that it will be better in the future, especially in the section on user satisfaction which will affect user ratings in interacting with the website. To support the research, the End-User Computing Satisfaction (EUCS) method is used to assist in calculating the quality assessment of the website which is divided into several variables. The EUCS method measures user satisfaction by making a comparison between the ratings that users have given on the assessment sheet that has been made with the existing service system (Brawijaya University Scholarship Website). There are 5 variables used in this study, namely Content, Accuracy, Format, Ease of Use, and Timeliness. The results obtained after testing were 2 variables that got unsatisfactory values, namely Format and Accuracy variables, but it cannot be denied that the other 3 variables, namely Content, Ease Of Use, and Timeliness had sufficient values ​​but did not escape input and criticism from respondents.